Servant Leadership and Teachers’ Emotional Exhaustion—The Mediation Role of Hindrance Stress and Depersonalization - Hongchao Wu; Jun Zhao; Shaoping Qiu; Xiuhong Li (Behavioral Sciences)
Abstract: This study aims to explore the impact of school servant leadership on teacher emotional exhaustion in the context of Chinese education, and analyze the mediating effects of teacher hindrance stress and depersonalization. Based on the Job Demand-Control-Support (JDCS) model and servant leadership theory, the research constructs a model for the influence mechanism of school servant leadership on teacher emotional exhaustion and validates it using Structural Equation Modeling (SEM). A total of 3751 primary and secondary school teachers from eight provinces in China participated in this study. The results indicate servant leadership demonstrates a strong negative relationship with emotional exhaustion, with hindrance stress and depersonalization serving as a sequential mediation between servant leadership and emotional exhaustion. This study offers a new perspective on how servant leadership can alleviate emotional exhaustion among teachers, and provides practical insights for optimizing educational management models and enhancing teacher mental well-being.